2009
DOI: 10.1002/jqs.1250
|View full text |Cite
|
Sign up to set email alerts
|

Conifer pollen abundance provides a proxy for summer temperature: evidence from the latitudinal forest limit in Finland

Abstract: Huusko, A. and Hicks, S. 2009. Conifer pollen abundance provides a proxy for summer temperature: evidence from the latitudinal forest limit in Finland.ABSTRACT: A 23-year record of pollen deposition (pollen accumulation rates: PARs) indicates that pollen production of the two most common northern boreal conifers -pine and spruce -varies dramatically from year to year and that high and low pollen years show consistency over the whole of northern Lapland. Testing for a calibration between the annual PARs of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 19 publications
3
44
0
Order By: Relevance
“…This may indicate the strong influence of climatic conditions on spruce pollen production. The studies of Autio and Hicks (2004) and Huusko and Hicks (2009) in Finland and of Van der Knaap and Van Leeuwen (2003) in Switzerland produced comparable results. The latter authors found that summer drought was essential for abundant pollen deposition of Picea in the following year.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This may indicate the strong influence of climatic conditions on spruce pollen production. The studies of Autio and Hicks (2004) and Huusko and Hicks (2009) in Finland and of Van der Knaap and Van Leeuwen (2003) in Switzerland produced comparable results. The latter authors found that summer drought was essential for abundant pollen deposition of Picea in the following year.…”
Section: Discussionmentioning
confidence: 72%
“…Annual pollen sums of both taxa demonstrate large year-to-year variation, which is controlled mainly by climatic factors such as summer temperature of the year before pollen emission (e.g. Hicks, 2001; Van der Knaap et al, 2001;Autio & Hicks, 2004;Pidek et al, 2008;Huusko & Hicks, 2009). On several occasions during pollen monitoring in Roztocze, as part of the PMP, no spruce pollen was recorded in the regional trap.…”
Section: Stressed That Even Ifmentioning
confidence: 99%
“…In Finland (Hicks 2006;Huusko and Hicks 2009;Kuoppamaa et al 2009), Northern Sweden (Barnekow et al 2007) and the Alps (Kamenik et al 2009) efforts are made to use PAR from fossil records to reconstruct past climate, specifically summer temperatures. This requires high resolution records with good temporal control, because only near-annual variations in PAR can be expected to reflect variations in temperature or precipitation in the way pollen trap records do.…”
Section: Par and Fossil Recordsmentioning
confidence: 99%
“…Whilst these methods do reduce the effects of climate-related inter-annual variability in plant flowering (e.g. Huusko and Hicks, 2009;Jackson and Kearsley, 1998), they would have blurred the signal of the coppice cycle which we seek to study due to variability in the ground vegetation throughout a coppice cycle being greater than the climatic influence between consecutive years (e.g. Waller, at al.…”
Section: Pollen Datamentioning
confidence: 99%